Wearable graphene-patterned gas detection sensor - Mohammadreza Nehzati; Alireza Barati Haghverdi; Amir Ali Mohammad Khani; Ilghar Rezaei; Toktam Aghaee (Results in Optics)
A wearable graphene-based bio-sensor is proposed in this work. The operational frequency range is the THz gap while the sensor includes a golden bottom, Kapton spacer, and periodic arrays of graphene disks and ribbons. The structure is exclusively represented by an impedance that can predict absorption versus frequency. Additionally, a parallel full wave simulation is performed to investigate the equivalent circuit model (ECM) validation. According to the reported simulation results, the proposed graphene-based sensor leverages both design methodology and sensible response to probable toxic gas existence. This stems from highly sensitive behavior against variations in the surrounding environment’s refractive index. The proposed graphene-based sensor is capable of showing perfect absorption peaks @ 2.5 THz, 5.5 THz, and 8.5 THz while each peak possesses 0.2 THz width. Ample results are provided to explore the sensor sensitivity against design parameters including the structure geometry, physical constants, and external stimulation. Additionally, carbon monoxide is considered to pollute the space with different concentrations. The sensor responses for this situation are investigated from 0 to 400 ppm and interpreted. It shows that a 100 ppm variation of carbon monoxide causes about a 1THz frequency shift. Such a highly sensitive optical sensor is in great demand for realizing healthcare monitoring systems.